Health literacy knowledge and experience survey: Cross-cultural adaptation and the psychometric properties of the Iranian nurse version - Akram Parandeh; Fatemeh Rahmati-Najarkolaei; Mohsen Saberi Isfeedvajani (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Nurses' knowledge and Experience with Health Literacy can affect the treatment process, improving the quality of health care and effectively communicating with all clients. Evaluation of nurses' knowledge and experience requires a reliable instrument. This study aimed to translate cross-cultural adaptation and testing of Health Literacy Knowledge and Experience Survey (HL-KES). MATERIALS AND METHODS: This cross-sectional methodological study was done during 2018-2019. The study was carried out in two stages: the first phase was designed to obtain a translation and cross-cultural equivalent of the (HL-KES), based on the World Health Organization (2018) and the Sousa and Rojjanasrirat (2011) Guidelines in six steps: preparation, forward translation, reconciliation, back translation, back translation review and pretesting and cognitive debriefing of the translated questionnaires. The second phase was conducted to evaluate the psychometric properties of the questionnaire. RESULTS: The content validity index and content validity ratio values of all items were >0.62 and 0.79, respectively. Based on the Kuder-Richardson formula, the reliability of the knowledge dimension was reported as 0.7. Furthermore, split-half coefficient for inter-rather reliability and test-retest were 0.76 and 0.96, respectively. The reliability of their experiences with the HL-KES was measured using Cronbach's alpha, in which it was 0.82. CONCLUSIONS: The Persian version of the instrument for assessing nurses' knowledge and experience with health literacy had good validity and reliability. It is recommended that it should be used in educational, clinical environments, and also in future research studies.